Response to "Prevent Stunting Booklet (BoCeSting) as an Educational Medium and its Influence on the Attitudes of Mothers Under Five on Stunting Prevention in the Archipelago" - Pius Weraman; Teta Puji Rahayu; Rozan Asyrofi Rakyan Risang Aji (Aloha International Journal of Health Advancement (AIJHA), 2025)
Letter to editor: abstract is not required